Diagnosis-related group prospective payment system in Poland – costs versus tariffs: the case of inguinal hernia - Macuda, Małgorzata (Prospektywny system finansowania w Polsce oparty na jednorodnych grupach pacjentów – koszty versus przychody: przykład przepukliny pachwinowej, 2018)
In the last 20 years many OECD countries have adopted some form of diagnosis-related group (DRG) prospective payment system to reimburse hospitals. In Poland, hospitals are also paid fixed prices, imposed by Narodowy Fundusz Zdrowia (NFZ) according to DRG, for patients treated. The aim of this paper is to calculate, analyze and compare the costs of patient conditions within the same DRG (F72 – inguinal hernia), collate these costs and the reimbursement from NFZ with the purpose of determining the net profit and then check if it matches bigger research samples. In order to realize the aim of the paper, a comparative and a content analysis of medicals documents and financial data were adopted, and Student’s t-test was performed. The Shapiro-Wilk test was applied to confirm the correctness of the research sample. The results revealed that the reimbursement for costs related to inguinal hernia treatment covers the costs of 90% of patient conditions from the research sample
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 3, s. 102-110
Keywords: DRG; Diagnosis-Related Groups; prospective payment system; hospitals; costs; JGP; jednorodne grupy pacjentów; prospektywny system finansowania; szpitale; koszty